Evaluation of a hierarchically-structured CuO@TiO2-Al2O3 oxygen carrier for chemical looping with oxygen uncoupling. (1st December 2017) - Tian, Xin; Wei, Yijie; Zhao, Haibo
Highlights: SATCS-derived CuO@TiO2 -Al2 O3 oxygen carrier was adopted in CLOU. Cyclic redox tests were performed to evaluate the physical and chemical stability. Combustion efficiency of over 97.2% was attained when using anthracite as fuel. Thermo-mechanical analysis (TMA) was conducted to interpret sintering resistance. Abstract: High redox reactivity as well as sufficient physical durability of the oxygen carrier (OC) is of critical importance for the successful implementation of chemical looping processes. In this work, CuO@TiO2 -Al2 O3 OC with hierarchical structure, which is a kind of CuO-rich, Al2 O3 -supported and TiO2 -stablized ternary combined metal oxides system, was prepared by the self-assembly template combustion synthesis (SATCS) method. Performance of the rationally designed OC was cyclically tested with H2 in a thermogravimetric analyzer (TGA), as well as with coal in a batch fluidized bed reactor. TGA results showed that both the reduction and oxidation reactivity of the OC exhibited a reinforcing process during the first few cycles and then stabilized within the next dozens of cycles, and no obvious reactivity degradation phenomenon was observed. Reaction characteristics of the OC were further examined by reacting with coal in a fluidized bed reactor. Several critical performance indexes, like carbon conversion rate, oxygen release rate and combustion efficiency at different temperatures were calculated and compared. Mutual promotion relationship between carbon conversion rate of the coal and oxygen release rate of the OC was observed. Moreover, 20 cycles of redox process with anthracite were further conducted at 900 °C to evaluate both the physical and chemical stability of the OC. Stable and high combustion efficiency (higher than 97.2%) was achieved during the cyclic fluidized bed test, and the subsequent physicochemical characterization indicated that neither CuAl2 O4 phase was formed nor serious sintering problem occurred within the used OC samples. Thermo-mechanical analysis (TMA) results demonstrated relatively high transformation temperature of the OC, which explains well its superior anti-sintering property. All in all, the SATCS-derived CuO@TiO2 -Al2 O3 OC exhibited distinguished advantages of preventing the side reaction between CuO and Al2 O3 to form copper aluminates as well as inhibiting the OC sintering, which could be a suitable OC candidate for commercial application in chemical looping with oxygen uncoupling (CLOU) processes.